Allergic disorders and socio‐economic status: a study of schoolchildren in an urban area of Makassar, Indonesia. Issue 7 (July 2015) - Hamid, F.; Wahyuni, S.; van Leeuwen, A.; van Ree, R.; Yazdanbakhsh, M.; Sartono, E.
Summary Background In urban centres of developing countries, there is great variation in socio‐economic status (SES) and lifestyle; however, little information is available on allergic disorders in groups with high‐ or low‐SES within the same urban area. Objective To determine the prevalence of allergic disorders and investigate risk factors related to them among high‐ and low‐SES schoolchildren in Makassar, the capital city of South Sulawesi, Indonesia. Method This cross‐sectional study was performed in 623 children originating from high‐ (N = 349) and low‐SES (N = 274) schools. Information on reported allergic symptoms and potential factors associated with allergic disorders was obtained by questionnaire. Specific IgE and skin prick test (SPT) reactivity were determined against aeroallergens [Dermatophagoides pteronyssinus (HDM) and cockroach]. Total IgE and helminth infections were also assessed. Result The prevalence of SPT to any aeroallergens was significantly higher in high‐SES than in low‐SES school (25% vs. 8%, P < 0.001, respectively). However, specific IgE against cockroach and total IgE were significantly lower in high‐ than in low‐SES children. Allergic symptoms were reported more often in low‐ compared to high‐SES children. Specific IgE to aeroallergens significantly increased the risk of SPT positivity to the same aeroallergen in the high‐, but not in the low‐SES children. In the high‐ but not in low‐SES, there was a significant positive association between SPT to HDM and wheeze. Similarly, cockroach skin reactivity and elevated BMI increased the risk of eczema in the high‐SES children only. Conclusion and Clinical Relevance Skin prick test is higher in high‐SES, whereas IgE and allergic symptoms are higher in low‐SES children. Specific IgE is a risk factor for being SPT‐positive, and SPT positivity is a risk factor for allergic symptoms but only in children of high‐ and not low‐SES school. Therefore, the socio‐economic status of a child might affect the diagnosis of allergic disease in a developing country.